2008
DOI: 10.1287/orsc.1070.0343
|View full text |Cite
|
Sign up to set email alerts
|

Identity Incentives as an Engaging Form of Control: Revisiting Leniencies in an Aeronautic Plant

Abstract: R esearch has long shown that organizations shape members' identities. However, the possibility that these identities might also be desired and that members might benefit from this process has only recently been explored. In a qualitative study of a French aeronautic plant, I demonstrate how an implicitly negotiated leniency between management and workers around the use of company materials and tools, on company time, to produce artifacts for personal use, enhances workers' identities. This leniency applies to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
146
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(153 citation statements)
references
References 57 publications
4
146
0
Order By: Relevance
“…It also echoes the, albeit largely informal, ways in which employers have long used gendered characteristics as well as indulgency patterns where a managerial 'blind eye' was turned for functional ends on non-work misbehavior such as informal sports (Gouldner, 1955). A formalization of both these processes has been noted recently in the field of diversity legislation (Janssens and Zanoni, 2005) and in a case of 'negotiated leniency' by management in order to appropriate work-based occupational identities as a form of control (Anteby, 2008). The 'just be yourself' approach therefore resonates not only with contemporary liberalist themes such as diversity, market rationalism and enterprise (Kunda and Ailon-Souday, 2005), but with what Sennett (1976) referred to over 30 years ago as the 'ideology of intimacy' whereby more of the self becomes an open economic concern (see also Hancock and Tyler, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also echoes the, albeit largely informal, ways in which employers have long used gendered characteristics as well as indulgency patterns where a managerial 'blind eye' was turned for functional ends on non-work misbehavior such as informal sports (Gouldner, 1955). A formalization of both these processes has been noted recently in the field of diversity legislation (Janssens and Zanoni, 2005) and in a case of 'negotiated leniency' by management in order to appropriate work-based occupational identities as a form of control (Anteby, 2008). The 'just be yourself' approach therefore resonates not only with contemporary liberalist themes such as diversity, market rationalism and enterprise (Kunda and Ailon-Souday, 2005), but with what Sennett (1976) referred to over 30 years ago as the 'ideology of intimacy' whereby more of the self becomes an open economic concern (see also Hancock and Tyler, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps this is why the 'liberal organization' (Courpasson, 2006) attempts to harness authentic expressions of self by drawing the private realm and its signifiers into the workplace, and thus making use of those aspects of employee selves that were previously barred or ignored by management or simply retained or protected by employees as a point of difference (also Anteby, 2008).…”
Section: ======================mentioning
confidence: 99%
“…Difficulties from status differences can occur because an occupational group's prestige, authority, and autonomy result from occupation members hiving off lower-status dirty work to subordinate occupation members and protecting occupational boundaries rather than collaborating with members of different occupations (e.g., Abbott, 1988;Bechky, 2003a;Anteby, 2010;Ranganathan, 2013). Difficulties over meanings can occur because occupation-specific identities and beliefs often make it hard for members of different occupations to understand and appreciate each other's actions (Perlow and Weeks, 2002;Bechky, 2003b;Bailyn, 2006;Anteby, 2008). And difficulties around expertise can occur because incompatible codes, routines, or protocols often make it challenging for members of an occupation to share knowledge with non-members (Barley, 1986;Carlile, 2002;Bailey, Leonardi, and Chong, 2010;Huising, 2014).…”
mentioning
confidence: 99%
“…Investigating the selective use of various desired identities as organizational control instruments in an aeronautic plant, Anteby (2008) found that managerial leniency enhanced workers' occupational identity. Diemer & Blustein (2006) examined the role of critical consciousness (the ability of individuals to assess and overcome socio-political barriers) as a predictor of career development among urban adolescents.…”
Section: The Antecedents Of Identity At the Individual Levelmentioning
confidence: 99%
“…However, the research in the broad literature on identity has identified some predictors of identity. Broadly, contextual antecedents (e.g., Dukerich, Golden, & Shortell 2002;Dutton et al, 1994;Gonzalez & Denisi, 2009;Mael & Ashforth, 1992) as well as demographic and personal attribute related antecedents (e.g., Anteby 2008;Diemer & Blustein, 2006;Jackson & Neville, 1998) have been examined. In this light, in Essay # 2, I address these voids by looking at contextual and personal attribute related factors that might influence entrepreneurial identity.…”
Section: Introductionmentioning
confidence: 99%